Synthesis of Putrescine Bisamides as Antimicrobial and Anti-Inflammatory Agents with Molecular Docking Studies - Vidavalur, Siddaiah; Kadiri, Sunanda Kumari; Yettula, Kumari; Rayavarapu, Srinuvasarao; Gajula, Mahaboob Basha; Nakka, Mangarao; Tadikonda, Ramu (Science and Technology: Developments and Applications Vol. 9, 2025)
Putrescine bis amides are one of the subclasses of naturally occurring polyamides. During the last two decades, several symmetrical and unsymmetrical putrescine bisamides have been isolated from Aglaia, Liberica, and Carydalis species. In this study, a new naturally occurring N1, N6-dihydrocinnamyl putrescine bisamide, JBIR-94, along with nine structural analogs and a series of substituted phenyl and alkyl putrescine bisamides have been synthesized from putrescine and appropriately substituted carboxylic acids, through carboxylic acid chlorides. Antimicrobial, 5-Lipooxygenase enzyme inhibitory, and antioxidant studies were performed for all synthesized compounds. Antimicrobial assay performed against human pathogenic bacteria and fungi. Zone of inhibition was determined using agar well diffusion method, and minimum inhibitory concentration (MIC) was determined by broth dilution assay. The 5-Lipoxygenase (PDB ID 308Y) X-Ray crystal structure was obtained from the Protein Data Bank and used in docking studies. Antioxidant activities of putrescine bisamides were performed through radical scavenging assay using DPPH and Superoxide radicals. Dihydrocinnamyl series of putrescine bisamides (4a-4i) showed good bioactivities compared to substituted phenyl (6a-6g) and diakyl (6h-6j) series of compounds. Among all compounds, 4h (methylenedioxy analog) and 4a (JBIR-94) showed good antimicrobial, anti-inflammatory, and antioxidant activities.